The importance of endogenous nutrition of chicks from divergent strains for growing tested by deutectomy - Gonzales, E [UNESP] (2008)
Effects of yolk sac removal (deutectomy) upon performance of chicks from three divergent strains were tested to evaluate the importance of endogenous nutrition on the post-hatch phase. Chicks from three different strains (Hy-Line W98, Cobb 500, and JA57) were submitted to a surgery procedure after hatching. Half of them had the residual yolk removed, and the other constituted a sham-deutectomized group. After operation, chicks were designated to a 3 x 2 factorial design (3 strains x 2 presence/absence of yolk sac), in a total of six experimental groups and ten replications of two to four birds. During 14 experimental days all birds were fed ad libitum a 21% CP and 3050 kcal/kg em mash diet. Data were analyzed by ANOVA, and Tukey's test (p<0.05). Relative yolk sac weights were similar among chicks from different breeders, averaging 11.7% to 13.5%. Comparing to sham-operated, deuctetomized chicks had lower weight gain at 7 and 14d, indicating that endogenous nutrition, via yolk sac, is very important to galliform birds whatever their strain. Hy-line deutectomized chicks gained 40% less body weight at the 7th day as compared to their sham counterparts. Analysis of the same criterion to Cobb and JA57 groups revealed a decrease of 16.1% and 10.8%, respectively, on weight gain efficiency. At the 14th rearing day, Hy-Line chicks had the lowest weight gain, followed by JA57s' and Cobbs'. The results suggested that chicks selected for fast growth are less dependent on endogenous nutrition, responding better when exogenous nutrition is associated to yolk assimilation.